Analysis of Speaking Proficiency in Children Aged 2-5 Years at Kelas Berenang Karawang Institution - Aris, Mohammad; Parancika, Rd Bily; Anum, Adelina (CV. Tripe Konsultan, 2023)
Early childhood has several aspects that need to be developed to be able to improve cognitive and psychomotor development. One of these aspects is language proficiency. At the age of 2-6 years is the golden age which is the age of children in the early days of their life in the world. This age is at the best development for the child's physique and brain. Similarly, speaking skills need to be trained from an early age in order to form more appropriate speaking skills. This research is a qualitative research conducted by reducing data, presenting data and drawing conclusions. The results of this study show that early children between 2-3 years still speak using syllables or final spoken words, while early children aged 4-5 years who have begun to enter preschool have begun to be able to form words by displaying morphemes, and syntax.